2009
DOI: 10.1007/s10157-009-0247-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease management in an academic internal medicine clinic

Abstract: Chronic kidney disease remains under-recognized and undertreated despite well-publicized guidelines and widespread use of routine eGFR reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Despite the publication of CKD practice guidelines, adoption among PCPs and nephrologists has been limited (7)(8)(9)(10). A survey involving 301 physicians who were presented a hypothetical with CKD showed that only 47% of nephrologists and 33% of internists could identify five of six laboratory tests indicated by guidelines (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the publication of CKD practice guidelines, adoption among PCPs and nephrologists has been limited (7)(8)(9)(10). A survey involving 301 physicians who were presented a hypothetical with CKD showed that only 47% of nephrologists and 33% of internists could identify five of six laboratory tests indicated by guidelines (7).…”
Section: Discussionmentioning
confidence: 99%
“…(6) However, studies have shown that primary care providers (PCPs) have limited knowledge of these guidelines (7)(8)(9)(10). There have been few interventions to improve adherence to CKD guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…The primary aims of treatment in patients with CKD are both to prevent or, at least slow, progression of CKD. However, available therapies are limited and include inhibitors of renin/angiotensin system (Locatelli et al, 2009;Morrow et al, 2010). However, these drugs are not able to completely block the progression.…”
Section: Suramin Inhibits Progression Of Renal Fibrosis 763mentioning
confidence: 99%
“…Given the high prevalence of CKD and cost of replacement therapies for ESRD, any treatment that halts or slows the progression of renal fibrosis has the potential to provide an immense medical, social, and economic benefit. At present, angiotensinconverting enzyme inhibitors and angiotensin II receptor type 1 blockers are clinically used to combat renal fibrosis (Locatelli et al, 2009;Morrow et al, 2010). However, these drugs are not able to completely stop the progression of renal fibrosis; in some conditions, such as aristolochic acid-induced renal fibrosis in rats, they are not effective at all (Debelle et al, 2004;Boor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…52 Multiple studies identified disparities in the care of patients with resident PCPs (versus faculty PCPs), in areas such as diabetes care, cancer screening, discharge follow-up, and readmission rates. 43,[57][58][59][60][61][62] Given those disparities, further research is needed in assessing resident competence via EPAs and in determining what factors predict worse outcomes in patients seen by residents to identify areas for intervention and find the balance between autonomy and supervision.…”
Section: Evaluating Resident Practice and Performancementioning
confidence: 99%